Collaborative networking and the use of ICT in new organizational communications - Silva-Giraldo, César Augusto; Rueda-Mahecha, Yohanna Milena; Moreno-Suárez, Angélica María (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
The article presents the challenges faced by MSMEs from the use of new organizational languages from the use of collaborative networks, seeking to understand and analyze the interaction of communities seeking through creative thinking the construction of networks and the use of technologies, based on the theories of change under a social approach, generating organizational competitiveness processes from the social and cultural changes of internal and external customers. To this end, the design of an organizational communication strategy aimed at micro, small and medium-sized enterprises was proposed.